The Italian species of the Chthonius ischnocheles group (Arachnida, Pseudoscorpiones, Chthoniidae), with reference to neighbouring countries - Gardini, Giulio (Zootaxa, 2021)
A taxonomic revision and a key to the Chthonius C.L. Koch, 1843 species of the ischnocheles group from Italy, with records from neighbouring countries, are provided. The following new species are described: Chthonius gallettii n. sp. (♂, locus typicus: Sicily, Ragusa Province, Ragusa, Grotta delle Lame 6009 Si/RG), Chthonius gentianae n. sp. (♂, Veneto, Treviso Province, Fregona, Pian del Cansiglio, Bus della Genziana 1000 V/TV), Chthonius herminii n. sp. (♂♀, Veneto, Treviso Province, Cavaso del Tomba, Costalunga, Speoncia del Diaol 1811 V/TV); Chthonius inguscioi n. sp. (♂♀, Apulia, Lecce Province, Presicce, Grotta Madonna della Rutta 533 Pu/LE), Chthonius lanai n. sp. (♂♀, Piedmont, Cuneo Province, Bernezzo, Pertus d’la Kassetta 1323 Pi/CN), Chthonius marciai n. sp. (♂, Sardinia, Nuoro Province, Dorgali, Grotta del Bue Marino 12 Sa/NU) and Chthonius nicolosii n. sp. (♂♀, Sicily, Catania Province, Nicolosi, Grotta Lunga 1029 Si/CT). The following new subjective synonymies are proposed: Chthonius malatestai Callaini, 1980 n. syn. of C. agazzii Beier, 1966; Chthonius ruffoi Caporiacco, 1951 n. syn. of C. densedentatus Beier, 1938; Chthonius mingazzinii Callaini, 1991 n. syn. of C. euganeus Gardini, 1991; Obisium megachelum Amary, 1840 n. syn. of C. ischnocheles (Hermann, 1804); Chthonius dalmatinus Hadži, 1930 n. syn. of C. ischnocheles (Hermann, 1804); Chthonius litoralis Hadži, 1933 n. syn. of C. ischnocheles (Hermann, 1804); Chthonius rhodochelatus Hadži, 1937 of C. ischnocheles (Hermann, 1804) (rest. syn.). Chthonius horridus Beier, 1934 (n. stat.) is upgraded from subspecies of C. doderoi Beier, 1930 and Chthonius reductus Beier, 1939 (n. stat.) from subspecies of C. ischnocheles (Hermann, 1804). A lectotype is designated for Chthonius rayi L. Koch, 1873. Twenty-eight species of Chthonius of the ischnocheles group are known at present from Italy, of which three are endemic to Sicily and two to Sardinia. New country records are established for Chthonius alpicola Beier, 1951 (Croatia and Slovenia); Chthonius guglielmii Callaini, 1986 (mainland France), Chthonius halberti Kew, 1916 and Chthonius ilvensis Beier, 1963 (Corsica); Chthonius pygmaeus Beier, 1934 (Switzerland), and Chthonius densedentatus Beier, 1938 (France, Italy, Switzerland, Slovenia, Croatia, Albania and Greece).